Selective metallization of amorphous-indium–gallium–zinc-oxide thin-film transistor by using helium plasma treatment. (14th February 2018) - Jang, Hun; Lee, Su Jeong; Porte, Yoann; Myoung, Jae-Min
Abstract: In this study, the effects of helium (He) plasma treatment on amorphous-indium-gallium-zinc-oxide ( a -IGZO) thin-film transistors (TFTs) have been investigated. The He plasma treatment induced a dramatic decrease of the resistivity in a -IGZO thin films from 1.25 × 10 6 to 5.93 mΩ cm. After 5 min He plasma treatment, the a -IGZO films showed an increase in carrier concentration to 6.70 × 10 19 cm −3 combined with a high hall mobility of 15.7 cm 2 V −1 s −1 . The conductivity improvement was linked to the formation of oxygen vacancies during the He plasma treatment, which was observed by x-ray photoelectron spectroscopy analysis. The a -IGZO films did not appear to be damaged on the surface following the plasma treatment and showed a high transmittance of about 88.3% at a wavelength of 550 nm. The He plasma-treated a -IGZO films were used as source/drain (S/D) electrodes in a -IGZO TFTs. The devices demonstrated promising characteristics, on pair with TFTs using Al electrodes, with a threshold voltage ( V T ) of −1.97 V, sub-threshold slope (SS) of 0.52 V/decade, saturation mobility ( μ sat ) of 8.75 cm 2 V −1 s −1, and on/off current ratio ( I on / I off ) of 2.66 × 10 8 .